Work Environment and Employee’s Commitment in Three Selected Institutions in Rivers State - Nwachukwu Precious Ikechukwu; Joy I.N. Ezeh; Oshogbunu Esther Ogochukwu; Ogulu Nkechinyere; Naagbo Dumle (International Journal of Engineering and Management Research, 2019)
The aim of this study is to investigate work environment and employee’s commitment in three selected Institutions such as Rivers State University, University of Port Harcourt and Ignatius Ajuru University of Education in Port Harcourt, Rivers State. For the purpose of this study, descriptive research design was used. Simple random sampling technique was respectively used to select the respondents for the study. Respondents for this study were fifty (60) made up of twenty-five (35) senior staff and twenty-five (25) junior staff. Structured questionnaires were used for data collection. The study findings indicate that, organization working environment had an impact on members as far as respondents are concerned. The study also revealed that employees’ will improve their performance if the problems identified during the research are tackled by the management. The problems are flexibility of working environment, work noise distraction, supervisor’s interpersonal relationship with subordinates, presence of job aid, the use of performance feedback and improve of work incentives in the organization so that to motivate employees to perform their job. In conclusion based on the findings the study recommended that, the organization needs to have periodic meetings with employees to air their grievances to management and serve as a motivating factor to the employees. Management should find ways and means of communicating their goals and strategies to their employees in order to achieve what the organization is in business for, its mission and vision.